2023
DOI: 10.1063/5.0146550
|View full text |Cite
|
Sign up to set email alerts
|

Chimera states in multiplex networks: Chameleon-like across-layer synchronization

Abstract: Different across-layer synchronization types of chimera states in multilayer networks have been discovered recently. We investigate possible relations between them, for example, if the onset of some synchronization type implies the onset of some other type. For this purpose, we use a two-layer network with multiplex inter-layer coupling. Each layer consists of a ring of non-locally coupled phase oscillators. While oscillators in each layer are identical, the layers are made non-identical by introducing mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…There is a very large and growing body of neuroscientific evidence to be brought to bear on the development of this heuristic model. Of particular interest moving forward will be empirical and mathematical models that employ concepts of synchrony (McMillen & Kopell, 2003), coupled oscillators (Medvedev et al, 2003), 'leaky oscillators' (Cannon & Kopell, 2015) and 'ring oscillators' (Andrzejak & Espinoso, 2023;Lee & Krischer, 2023).…”
Section: Coordination In Time (Via Phase)mentioning
confidence: 99%
“…There is a very large and growing body of neuroscientific evidence to be brought to bear on the development of this heuristic model. Of particular interest moving forward will be empirical and mathematical models that employ concepts of synchrony (McMillen & Kopell, 2003), coupled oscillators (Medvedev et al, 2003), 'leaky oscillators' (Cannon & Kopell, 2015) and 'ring oscillators' (Andrzejak & Espinoso, 2023;Lee & Krischer, 2023).…”
Section: Coordination In Time (Via Phase)mentioning
confidence: 99%
“…In the original studies chimera states were reported in systems of identical oscillators with nonlocal connectivity, while later studies have demonstrated emerging chimeras under local, nonlocal or global connectivity schemes with delays and/or with non-identical elements [8]. A important characteristic of the typical chimera state was the frequency deviation in the incoherent regions: while all elements of the coherent regions have the same frequency of oscillations, the frequencies vary drastically in the incoherent regions [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%